LEARNING ISLAMIC RELIGIOUS EDUCATION DURING THE COVID-19 PANDEMIC - Darmi (Asosiasi Dosen Perguruan Tinggi Islam, 2020)
The Covid-19 pandemic has caused many changes in the education sector; learning is currently being carried out by paying attention to social distancing, resulting in very significant changes in learning methods. Learning Islamic Religious Education is one that is affected by this. The purpose of this article is to find out how the learning process of Islamic Religious Education during the Covid-19 pandemic, the learning media used, the effectiveness of learning, and the challenges faced. The research method used is library research, where this article will describe the latest and updated conditions of Islamic Religious Education learning. The results showed that learning Islamic Religious Education was carried out without face-to-face. Learning was carried out online, starting from the elementary school level to college; only at the early childhood level learning was carried out at home. The learning media used are entirely technology-based by utilizing the internet. The effectiveness of learning cannot be concluded because of the lack of data sources. The big challenge faced is the decline in student morale when learning is done online. It takes a special good learning format for learning Islamic Religious Education so that the learning objectives can be achieved.